“BRIDGING THE UNIVERSITY-INDUSTRY GAP ESSENTIAL FOR A SUSTAINABLE FUTURE” – MUTHARASU - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
The role of a Director for Industry Network at the Division of Industrial and Community Network (BJIM) Universiti Sains Malaysia (USM) is truly challenging in ensuring close ties between the university and its external partners. These include the multinational companies (MNCs), the small and medium enterprises (SMEs) as well as the nongovernmental organisations in order to attract funds for investments and more importantly, to establish collaborations and consolidate efforts to develop a culture that is “discoverydriven” for the university and in creating an “innovationdriven environment” among the industries.